Exploring Student-Centered Learning as a Tool to Prevent Radicalization in Islamic Junior Schools: A Case Study of Indonesia and Bangladesh - Sekar Ayu Aryani; Waston; Mahmudulhasan; Erham Budi Wiranto; Ahmad Asroni; Siti Fauziah; Muhamad Yusup (Jurnal Pendidikan Agama Islam, 2024)
Purpose – The peace and stability of society are seriously threatened by youth radicalization, particularly in educational environments. This study examines how critical thinking, inclusion, and active student involvement in Student-Centered Learning (SCL) can prevent radicalization in Islamic junior schools in Indonesia and Bangladesh. Through problem-solving and open communication, SCL exposes students to a variety of viewpoints and fosters critical thinking, which lessens their vulnerability to extremist beliefs. Design/methods/approach – Employing qualitative techniques, such as teacher and student interviews, the research delves into the distinct implementation obstacles of SCL in each nation. Findings – Results show that although SCL promotes respect for one another and critical thinking, its efficacy is limited by a systemic dependence on conventional techniques, a lack of resources, and inadequate teacher preparation.  Research implications/limitations – The study emphasizes how important it is to have resources, support at the policy level, and professional development in order to adequately utilize SCL as a deterrent to radicalization. For educational policymakers and groups seeking to establish safe and welcoming learning environments in Bangladesh, Indonesia, and other comparable countries, these findings provide insightful information.